Credit insurance what is it? : why do you need it? : what can it do for your business? - Bridgman, Terry (Lannoo Campus in association with Euler Hermes, 2013)
Credit Insurance is a book that offers a better understanding of credit insurance activities and seeks to communicate them to the world of business